Gem‐Diethyl Pyrroline Nitroxide Spin Labels: Synthesis, EPR Characterization, Rotamer Libraries and Biocompatibility. Issue 8 (14th May 2019) - Bleicken, Stephanie; Assafa, Tufa E.; Zhang, Hui; Elsner, Christina; Ritsch, Irina; Pink, Maren; Rajca, Suchada; Jeschke, Gunnar; Rajca, Andrzej; Bordignon, Enrica
Abstract: The availability of bioresistant spin labels is crucial for the optimization of site‐directed spin labeling protocols for EPR structural studies of biomolecules in a cellular context. As labeling can affect proteins' fold and/or function, having the possibility to choose between different spin labels will increase the probability to produce spin‐labeled functional proteins. Here, we report the synthesis and characterization of iodoacetamide‐ and maleimide‐functionalized spin labels based on the gem ‐diethyl pyrroline structure. The two nitroxide labels are compared to conventional gem ‐dimethyl analogs by site‐directed spin labeling (SDSL) electron paramagnetic resonance (EPR) spectroscopy, using two water soluble proteins: T4 lysozyme and Bid. To foster their use for structural studies, we also present rotamer libraries for these labels, compatible with the MMM software. Finally, we investigate the "true" biocompatibility of the gem ‐diethyl probes comparing the resistance towards chemical reduction of the NO group in ascorbate solutions and E. coli cytosol at different spin concentrations. Abstract : Conserving the spin : The synthesis and characterization of iodoacetamide‐ and maleimide‐functionalized spin labels based on the gem ‐diethyl pyrroline structure has been reported. The two nitroxide labels are compared to conventional gem ‐dimethyl analogs by site‐directed spin labeling (SDSL) electron paramagnetic resonance (EPR) spectroscopy, using two water soluble proteins (see Figure: comparing the structures of three nitroxide labels attached to a cysteine residue)